2013
DOI: 10.1164/rccm.201207-1270oc
|View full text |Cite
|
Sign up to set email alerts
|

An Association between l-Arginine/Asymmetric Dimethyl Arginine Balance, Obesity, and the Age of Asthma Onset Phenotype

Abstract: Rationale: Increasing body mass index (BMI) has been associated with less fractional exhaled nitric oxide (FE NO ). This may be explained by an increase in the concentration of asymmetric dimethyl arginine (ADMA) relative to L-arginine, which can lead to greater nitric oxide synthase uncoupling. Objectives: To compare this mechanism across age of asthma onset groups and determine its association with asthma morbidity and lung function. The log of plasma L-arginine/ADMA was inversely correlated with BMI in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
117
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(129 citation statements)
references
References 44 publications
9
117
1
2
Order By: Relevance
“…Our measured concentrations of ADMA, SDMA and arginine in EBC samples are similar to those reported in healthy adolescents [51] and adults [55]. We did not observe significant differences in BMI-classified patients on concentrations of ADMA, arginine/ADMA or nitrate/ ADMA ratios in EBC or plasma samples, but these may be specific findings to obesity-related asthma [22].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our measured concentrations of ADMA, SDMA and arginine in EBC samples are similar to those reported in healthy adolescents [51] and adults [55]. We did not observe significant differences in BMI-classified patients on concentrations of ADMA, arginine/ADMA or nitrate/ ADMA ratios in EBC or plasma samples, but these may be specific findings to obesity-related asthma [22].…”
Section: Discussionsupporting
confidence: 87%
“…Endothelial NOS dysfunction decreases NO-dependent vasodilation and contributes to hypertension and other cardiovascular complications often seen with obesity [20]. Recent studies focused on obesity-related asthma in adults suggest that obese adult asthmatics have a reduced fractional NO concentration in exhaled air (FeNO) related to an impairment in the arginine/ADMA pathway [22,23]. Moreover, FeNO increases in morbidly obese patients without asthma after weight loss following bariatric surgery [24].…”
Section: Introductionmentioning
confidence: 99%
“…It was also decreased in obese asthmatics compared to non-obese asthmatics. Reduced arginine / asymmetric dimethyl arginine ratio in obesity may explain this phenomenon [26]. The negative correlation between FeNO and the female gender (who made up ~65% of subjects) compared to males may also be influencing this finding.…”
Section: Discussionmentioning
confidence: 95%
“…Others have shown that there is a negative correlation between BMI and FeNO in asthma [25]. Investigators have demonstrated increased asymmetric di-methyl arginine compared to Larginine in obesity [26]. This uncouples NO synthase leading to lowered FeNO.…”
Section: Introductionmentioning
confidence: 99%
“…To define pathways to explain differences in inflammatory patterns in obese patients with asthma, Holguin and colleagues measured the formation of asymmetric dimethyl arginine (ADMA), a product of posttranslational methylation of L-arginine and an L-arginine analog that inhibits both the inducible and constitutive forms of nitric oxide synthases (18). ADMA formation results in uncoupling of nitric oxide synthase, reduced NO synthesis, and increased oxidant production, and ADMA is increased in obesity (19).…”
Section: Obesitymentioning
confidence: 99%